The Crime of Abuse of Power and Ways to Confront It - صالح, رزگار عبدالكريم (Sulaimani Journal for Humanities, 2025)
Abuse of power is considered as one of the most serious crimes which threatens the trust between citizens and state institutions, and it has negative impacts and destructive results on society as well as state institutions infrastructure; this would lead to mistrust of citizens in official institutions for the lack of equality in front of benefits of public utilities and limiting it on determined people. All these reasons has caused the abuse of power phenomenon to be a high saner on the international level or national therefore, the need to address the phenomenon is emerged either legislatively or procedurally in a clear and effective manner. At the national level, many states have passed legislations and taken strides to overcome the phenomenon of abuse of power that is by criminating the act and combating it so that to block the influential people from entering the public power as they would like. At the international level as well, states have realized that their internal legislations are not enough to overcome the act; therefore, they have enacted international conventions to confront corruption which include preventive measurements to limit the corruption and , as part of it, abuse of power.